Pemilihan Supplier Metal End Menggunakan Metode Analytic Hierarchy Process (AHP) pada PT AMI - Kusumawati, Nita Machvira; Indriastiningsih, Erna; Nugrahadi, Bekti (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Supplier selection is a strategic process that plays a crucial role in ensuring smooth production and the quality of the final product. PT AMI, an export-oriented garment company, faces challenges in selecting metal end suppliers because the selection process has been subjective, relying solely on price comparisons and neglecting other relevant criteria. This has led to inconsistent material quality, delivery delays, and a high rate of product defects. This study aims to apply the Analytic Hierarchy Process (AHP) method to determine the best supplier based on a multicriteria evaluation involving five main criteria: quality, price, delivery, payment, and procedure, with a total of 18 subcriteria. Data were collected through interviews and questionnaires with three respondents from relevant departments (Quality Control, Purchasing, and Production). The AHP results indicate that quality is the most influential criterion, with a weight of 0.528, followed by price (0.197), delivery (0.125), payment (0.082), and procedure (0.068). Among the three supplier alternatives, Magic Trim LTD was selected as the best supplier with a final weight of 0.5759. The AHP method has proven effective in supporting companies in making more objective and measurable decisions when selecting suppliers. Keywords: Analytic Hierarchy Process (AHP), Metal End, Multicriteria, Supplier Selection